DESAIN APLIKASI PEMBELAJARAN MOBILE BAHASA DAN BUDAYA JEPANG - Rizka; Administrator Jurnal; Afif (AGENTS: Journal of Artificial Intelligence and Data Science, 2021)
This research aims to build a Japanese language and culture learning application using Android platform. It supports mobile learning so it can be accessed easily anywhere and anytime. It also provides an interesting learning experience with various and interactive features. This research consist of six stages: literature study, data collection, analysis, design, implementation, and testing. System design and development use a waterfall method. The system testing used is Blackbox and questionnaires. This research produces a Japanese learning mobile application which consists of an introduction to Hiragana and Japanese culture, learning materials, and evaluation. Blackbox test results show that all features function according to their function. This research also uses a questionnaire to find out the user responses about the application. The results show that 85.7% of respondents believe that this application is easy to use and 64.3% rate it provides material content that can be understood easily.